Study about Multicriteria Evaluation and Geographic Information Systems - Bussolini, Adrián Oscar; Renzo, Ana Elvira Di (Current Advances in Geography, Environment and Earth Sciences Vol. 3, 2022)
This work proposes the best strategy for the "Location of the integral waste processing center for the metropolitan area in the city of Rosario". This would be achieved with the Multi criteria evaluation, which can be defined as a set of techniques oriented to assist in the decision making process. The criteria are one of the fundamental elements of the Multi Criteria Evaluation, in which the success or failure of the developed evaluation will largely depend on its correct choice. It is based on the development and application of two mathematical models of decision support based on the ELECTRE method and the Analytical Hierarchical Processes known as AHP method.